Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s11524-011-9543-z
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-Level Factors Associated with Physical Dating Violence Perpetration: Results of a Representative Survey Conducted in Boston, MA

Abstract: Neighborhood-level characteristics have been found to be associated with different forms of interpersonal violence, but studies of the relationship between these characteristics and adolescent dating violence are limited. We examined 6 neighborhood-level factors in relation to adolescent physical dating violence perpetration using both adolescent and adult assessments of neighborhood characteristics, each of which was aggregated across respondents to the neighborhood level. Data came from an in-school survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
75
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 66 publications
2
75
0
4
Order By: Relevance
“…However, scientific research (Capaldi & Owen, 2001;Rothman et al, 2011;Timmons Fritz & Smith-Slep, 2009) has mostly addressed physically violent behaviours. The possibility of objectifying behaviours such as pushing, kicking, grabbing, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, scientific research (Capaldi & Owen, 2001;Rothman et al, 2011;Timmons Fritz & Smith-Slep, 2009) has mostly addressed physically violent behaviours. The possibility of objectifying behaviours such as pushing, kicking, grabbing, etc.…”
mentioning
confidence: 99%
“…No obstante, los comportamientos violentos de carácter físico han sido los más atendidos por los trabajos científicos (Capaldi y Owen, 2001;Rothman et al, 2011;Timmons Fritz y Smith-Slep, 2009). La posibilidad de objetivación que tienen comportamientos como empujar, patear, agarrar, etc.…”
unclassified
“…Population-based surveys within the United States (Schafer et al, 1998;Smith et al, 2011;Whitaker et al, 2007) and the United Kingdom (Graham et al, 2004) have found that rates of FMPV equal or exceed the rates of MFPV. Of note, adolescent females perpetrate dating violence at higher rates than their male peers (Jain et al, 2010;Magdol et al, 1997;Rothman et al, 2011). Women, however, are more likely than men to sustain injury as a result of IPV (Archer, those who did most of their drinking in bars (and also drank in other venues) were signifi cantly more likely to report arguments and fi ghting in the past 12 months compared with those who were light drinkers.…”
mentioning
confidence: 99%
“…Although these studies have looked at violence of all types -verbal, sexual, coercive, relational and physical -most of the resulting literature has focused on physical violence (Capaldi and Owen, 2001;O'Donohue, Downs and Yeater, 1998;Rothman et al, 2011;Timmons and Slep, 2009), probably because of its unexpectedly high prevalence. The data collected is alarming, revealing aggression levels of 31% and 26% respectively for boys and girls (Simon, Miller, Gorman-Smith, Orpinas and Sullivan, 2010), but a number of studies have urged caution when evaluating this prevalence, drawing attention to the variety of types of aggression that may be covered under the single construct of "physical violence" and their relative sig-nificance taking into account other background variables.…”
Section: Introductionmentioning
confidence: 99%